Evaluasi Penggunaan Rekam Medis Elektronik oleh Tenaga Kesehatan Berdasarkan Metode HOT-Fit di RSUD Majalengka - Vidiya Kartika; Fitria Dewi Rahmawati; Totok Subianto; Elfi Elfi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
The implementation of Electronic Medical Records (EMR) has become mandatory for healthcare facilities as part of the digital transformation of healthcare to improve service quality. This study aims to evaluate the use of EMR among healthcare workers based on the Human, Organization, and Technology-Fit (HOT-Fit) framework in order to identify the factors influencing its implementation and overall effectiveness. This study aims to evaluate the use of EMR by healthcare workers based on the HOT-Fit method at Majalengka Regional General Hospital. This study used a quantitative descriptive design with a cross-sectional approach. A sample of 86 healthcare workers was selected using a proportionate stratified random sampling technique. Data were collected using a valid and reliable HOT-Fit-based questionnaire, then analyzed descriptively. Shows that all variables are in the good category, namely human (77%), organization (77%), technology (76%), and net benefit (77%). The implementation of EMR has been running well, but still requires improvement, especially in the technological aspect as well as strengthening organizational support and user understanding.